Leadership Crisis: Concepts, Theories, and Methods, An Anthropological Perspective (Global Journal of Science Frontier Research, 2020)
The purpose of the study is to make a critical assessment of concepts, theories/models and methods for the study of leadership and its crisis. The central research question is "is there a matching of leadership with right time, right content, and right decision?"Historical archival content analysis based on the review of literature was the method used for preparing this paper. The declaration of Nepal as a republic is a historical political achievement. However, the attempt to abolish monarchy have been made even earlier in the 1950 's, 1960's, 1970's, or even in 1979, 1989, 1996,or2006. But finally, Nepal as a republic was declared on May 28, 2008.
Keywords: leadership; leadership theories; methods; crisis; decision-making; political parties